2016
DOI: 10.1038/bjc.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

High level of interleukin-10 in serum predicts poor prognosis in multiple myeloma

Abstract: Background:Interleukin-10 (IL-10) is a inhibiting inflammatory cytokine that plays an important role in immune suppressive microenvironment in multiple myeloma (MM). Whether the level of serum IL-10 could predict treatment response and survival outcomes or not needs to be investigated in MM patients.Methods:The level of IL-10 in serum was measured using enzyme-linked immunosorbent assay in 188 patients with newly diagnosed MM.Results:The best cutoff value for IL-10 in predicting survival is 169.69 pg ml−1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…The prognosis of MM patients was influenced by IL‐10. Wang et al demonstrated that the MM patients with high serum level of IL‐10 had shorter OS and progression‐free survival than those with low serum level of IL‐10 . Likewise, the IL‐10 −592 CA and CC (high‐producer type) genotypes were significantly associated with poor survival in the present study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The prognosis of MM patients was influenced by IL‐10. Wang et al demonstrated that the MM patients with high serum level of IL‐10 had shorter OS and progression‐free survival than those with low serum level of IL‐10 . Likewise, the IL‐10 −592 CA and CC (high‐producer type) genotypes were significantly associated with poor survival in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, there was no significant difference in IL‐10 and IL‐10R polymorphisms between the control group and the MM group, and these results suggested that the IL‐10 and IL‐10R polymorphisms are not implicated in the susceptibility to MM of the Japanese. Some investigators have suggested that a high serum level of IL‐10 is correlated to a high stage of disease according to the ISS and the Durie and Salmon classification . A high level of IL‐10 has also been demonstrated in the serum of MM patients with light chain disease and renal failure .…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in the low IL-10 group had superior survival compared with those in the high IL-10 group (3-year PFS rate: 69.3% versus 13.3%; 3-year OS rate: 93.6% versus 51.9%). Multivariate analysis confirmed that high serum IL-10 concentrations at diagnosis was an unfavourable factor for PFS and OS [ 210 ].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 96%
“…19 The survival time in various hematologic malignancies and ovarian cancer has been reported to be negatively correlated with the levels of IL-10. 20,21 In ALS, the role of IL-10 has only been studied in a small cohort. One previous retrospective study of 29 patients found that higher plasma IL- Abbreviations: ALS = amyotrophic lateral sclerosis; HR = hazard ratio; IFN-α = interferon alpha; IL = interleukin; NA = not applicable; n analyzed = number of patient samples analyzed; n LLOD = number of samples in this analysis with cytokine levels below lower limit of detection; OMND = other motor neuron disease; TNF-α = tumor necrosis factor alpha; TRAIL = TNF-related apoptosis-inducing ligand.…”
Section: Immunopathologic Processes Related To Als Genetic Variantsmentioning
confidence: 99%